A novel method for treating complete rectal prolapse with laparoscopic sigmoidopexy to the abdominal wall: A case report. (October 2022) - Takahashi, Junji; Yoshida, Masashi; Kamada, Teppei; Suzuki, Norihiko; Ohdaira, Hironori; Suzuki, Yutaka
Abstract: Introduction: The existing treatment methods for rectal prolapse still have problems in terms of their recurrence, invasiveness, and complications; hence, minimally invasive techniques with fewer recurrences and complications are necessary. We performed laparoscopic sigmoidopexy to the abdominal wall to treat complete rectal prolapse. Presentation of case: An Asian woman in her 80s presented with a complaint of constant faecal and urinary incontinence. She was diagnosed with a 4 cm complete rectal prolapse and underwent surgery. The sigmoid colon was tractioned laparoscopically and fixed to the abdominal wall. The patient had no intraoperative or postoperative complications, and her defaecation was well-controlled without recurrence for one year after surgery. Discussion: In this study, we performed laparoscopic sigmoidopexy to the abdominal wall with good results. Conclusion: This simple method, which requires only five sutures, can be a candidate treatment method for complete rectal prolapse. Highlights: This is the first reported case of abdominal wall fixation for rectal prolapse. Laparoscopic fixation of the abdominal wall with minimal dissection was performed. Repair is possible without the use of artificial material. The procedure requires only five sutures to fix. This method may be a useful option for patients who can undergo general anaesthesia.